2006
DOI: 10.1073/pnas.0607053103
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme therapy in mannose receptor-null mucopolysaccharidosis VII mice defines roles for the mannose 6-phosphate and mannose receptors

Abstract: Enzyme replacement therapy (ERT) is available for several lysosomal storage diseases. Except for Gaucher disease, for which an enzyme with exposed mannosyl residues targets mannose receptors (MR) on macrophages, ERT targets primarily the mannose 6-phosphate receptor (MPR). Most recombinant lysosomal enzymes contain oligosaccharides with both terminal mannosyl and mannose 6-phosphate residues. Effective MPR-mediated delivery may be compromised by rapid clearance of infused enzyme by the MR on fixed tissue macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 24 publications
3
52
0
Order By: Relevance
“…Similar results were obtained in the mouse model of MPS II (29), aspartylglycosaminuria (30), α-mannosidosis (31), and metachromatic leukodystrophy (32). To account for enzyme delivery to adult brain, we speculated that increasing the enzyme dose saturated the clearance receptors in visceral tissues, thus delaying clearance of the enzyme from the circulation and allowing uptake by receptors expressed on the BBB (28,33).…”
supporting
confidence: 60%
“…Similar results were obtained in the mouse model of MPS II (29), aspartylglycosaminuria (30), α-mannosidosis (31), and metachromatic leukodystrophy (32). To account for enzyme delivery to adult brain, we speculated that increasing the enzyme dose saturated the clearance receptors in visceral tissues, thus delaying clearance of the enzyme from the circulation and allowing uptake by receptors expressed on the BBB (28,33).…”
supporting
confidence: 60%
“…Low levels of brain entry were implicated to account for the effects, even though disappearance of these proteins from serum was reported to occur in minutes. More recently, it has been suggested that slowing clearance of the recombinant enzyme from the circulation could further improve CNS pathology in MPS VII mice (37,38). The LV-mediated erythroid-specific gene therapy approach developed here could provide continuously higher than normal IDUA in the circulation with potential lifelong CNS therapeutical benefits, although the precise mechanisms for CNS entry are to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, alterations in the transport of a lysosomal enzyme across the BBB occur with postnatal development, which limits the effectiveness of ERT to adults. Sly et al (6) and Stahl et al (7) have demonstrated that the terminal half-life of P-GUS is Ϸ5 min after i.v. injection in MPS VII mice and plasma clearance of P-GUS is predominantly mediated by the mannose receptor in vivo.…”
mentioning
confidence: 99%
“…Epinephrine is known to increase plasma mannose levels immediately after injection in rats (27). Because a large fraction of injected P-GUS is normally cleared by the mannose receptor in the liver (6,15,28), the mannose could transiently inhibit mannose receptor uptake and increase the P-GUS available to the newly expressed M6P receptors on brain capillaries.…”
mentioning
confidence: 99%